Navigating the authority paradox: Practising objectivity in environmental expertise. Issue 67 (January 2017) - Kunseler, Eva-Maria; Tuinstra, Willemijn
Highlights: The call for objective science is reinforced when the objectivity of experts is publicly called into question. Institutionalised forms of scientific advice to governments are faced with this 'authority paradox'. The paradigmatic case shows how environmental experts adhere to different conceptions of objectivity. Reflexive skills enable experts to recognise which meanings of objectivity are invoked in public debates. Abstract: We empirically reveal how environmental experts interpret the objectivity norm while navigating the authority paradox. The paradox here is that while there is a need for objective scientific advice, such advice is only to be acquired from experts and expert agencies whose objectivity and, hence, authority are contested. Viewed through the lens of practice, we identify what practitioners at the PBL Netherlands Environmental Assessment Agency understand by objectivity. Using this paradigmatic case, we show how practitioners renegotiate the meaning of objectivity while seeking to engage with new policy actors and extended peers in an independent, rigorous and legitimate manner. Successfully navigating the authority paradox is related to skilfully representing and adapting to various meanings of objectivity. Experts and experts agencies accordingly need reflexive skills to recognise which meanings of objectivity they ascribe to and which ones are invoked in public debates. Environmental experts who are able to loosely connect diverse objectivity conceptions are more likely considered as trustworthy and authoritative partners in environmental science-policy interfaces.